DENSpm overcame Bcl-2 mediated resistance against Paclitaxel treatment in MCF-7 breast cancer cells via activating polyamine catabolic machinery - Akyol, Zeynep; Çoker Gürkan, Ajda; Palavan Ünsal, Zeynep Narçın; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (Elsevier France-Editions Scientifiques Medicales Elsevier, 23 Rue Linois, 75724 Paris, France, 2016)
Purpose: The Bcl-2 mediated resistance is one of the most critical obstacle in cancer therapy. Conventional chemotherapeutics such as Paclitaxel, a commonly used in the treatment of metastatic breast cancer, is not sufficient to overcome Bcl-2 mediated drug resistance mechanism. Thus, combinational drug regimes are favored by researchers to overcome resistance phenotype against drugs. N1, N11-diethylnorspermine (DENSpm), a polyamine analogue, which is a promising drug candidate induced-cell cycle arrest and apoptosis in various cancer cells such as prostate, melanoma, colon and breast cancer cells via activated polyamine catabolism and reactive oxygen generation. Recent studies indicated the potential therapeutic role of DENSpm in phase I and II trials in breast cancer cases. Although the molecular targets of Paclitaxel in apoptotic cell death mechanism is well documented, the therapeutic effect of DENSpm and Paclitaxel in breast cancer cells has not been investigated yet. In this study, our aim was to determine the time dependent effect of DENSpm and Paclitaxel on apoptotic cell death via determination of polyamine metabolism related targets in wt and Bcl-2 overexpressing MCF-7 breast cancer cells. Results: In our experimental study, Paclitaxel decreased cell viability in dose-dependent manner within 24 h. Co-treatment of Paclitaxel (30 nM) with DENSpm (20 mu M) further increased the cytoxicity of Paclitaxel (30 nM) compared to alone Paclitaxel (30 nM) treatment in MCF-7 Bcl-2+ breast cancer cells. In addition, we determined that resistance against Paclitaxel-induced apoptotic cell death in Bcl-2 overexpressed MCF-7 cells was overcome due to activation of polyamine catabolic pathway, which caused depletion of polyamines. Conclusions: DENSpm combinational treatment might increase the effect of low cytotoxic paclitaxel in drug-resistant breast cancer cases. (C) 2016 Elsevier Masson SAS. All rights reserved.
Keywords: Paclitaxel; DENSpm; Apoptosis; Polyamine; Breast cancer